2017
DOI: 10.1016/j.neuroimage.2017.05.067
|View full text |Cite
|
Sign up to set email alerts
|

The energy landscape underpinning module dynamics in the human brain connectome

Abstract: Human brain dynamics can be viewed through the lens of statistical mechanics, where neurophysiological activity evolves around and between local attractors representing mental states. Many physically-inspired models of these dynamics define brain states based on instantaneous measurements of regional activity. Yet, recent work in network neuroscience has provided evidence that the brain might also be well-characterized by time-varying states composed of locally coherent activity or functional modules. We study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
60
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 54 publications
(63 citation statements)
references
References 96 publications
(196 reference statements)
3
60
0
Order By: Relevance
“…Our analyses extend previous 133 research that has found network flexibility successfully characterizes large-scale functional differences 134 (e.g., Telesford et al, 2016) in executive function (Braun et al, 2015) and mood (Betzel et al, 2017). 135 Allegiance, on the other hand, has been used to describe observed network dynamics on a finer scale, 136 estimating alignment with a pre-defined functional architecture (Bassett et al, 2015) as well as 137 identifying transitions among certain network configurations (Ashourvan et al, 2017). Across the set 138 of network science metrics adapted for neuroscience application (for review, see Garcia et al, 2018), 139 allegiance and flexibility are the best suited to identify changes in scales of processing.…”
Section: Introduction 40supporting
confidence: 66%
“…Our analyses extend previous 133 research that has found network flexibility successfully characterizes large-scale functional differences 134 (e.g., Telesford et al, 2016) in executive function (Braun et al, 2015) and mood (Betzel et al, 2017). 135 Allegiance, on the other hand, has been used to describe observed network dynamics on a finer scale, 136 estimating alignment with a pre-defined functional architecture (Bassett et al, 2015) as well as 137 identifying transitions among certain network configurations (Ashourvan et al, 2017). Across the set 138 of network science metrics adapted for neuroscience application (for review, see Garcia et al, 2018), 139 allegiance and flexibility are the best suited to identify changes in scales of processing.…”
Section: Introduction 40supporting
confidence: 66%
“…Therefore, we hypothesize that examination of the correlational structure of the estimated input should reveal that the ROIs within the intrinsically connected networks (or, resting state networks) in general also receive coherent (i.e., correlated) input. Moreover, it has been shown that at the large scale the resting state networks are roughly organized into three functionally coherent groups that form the basis of the main dynamic attractor states of the system (2). Therefore, we conjecture that the coherent output of these large-scale systems are in part the result of the coherent input to these systems.…”
Section: Hierarchical Organization Of Inputs To the Brainmentioning
confidence: 79%
“…At the ecological "behavior" scale (policies), these local minima provide a comprehensive re-description of affordances that unites the exteroceptive with the proprio-and interoceptive dimensions (Pezzulo and Cisek, 2016). They also generalize to the sub-ecological "action" scale, as reflex arcs, grounded in the physics of nerve electricity Sengupta et al, 2013), and the supra-ecological "activity" scale, as extended active and resting states, grounded in physiological homeostasis/allostasis dynamics (Ashourvan et al, 2017). 6. sKatinG UnCertainty: GeneraLiZed aFFordanCe tHeory, sKiLLed eXpertise, and tHe FraMe proBLeM This section considers how local minima of uncertainty in the projected temporal sequence of generative model states serve to unify developmental theory and the underspecified (by Gibson) notion of learned affordances. We then show concrete applications in skilled practical and cultural activities.…”
Section: Free Energy Revisitedmentioning
confidence: 99%